Pola Curah Hujan di Provinsi Indonesia Saat El-Nino dan La-Nina: Analisis Periodogram FFT dan Lomb - Nugraheni, Melly; Zakaria, Ahmad; Wahono, Endro Prasetyo; Kusumastuti, Dyah Indriana; Herison, Ahmad (Department of Civil Engineering, Diponegoro University, 2024)
Indonesia is a country affected by the El Nino and La Nina climate anomalies. The provinces of Aceh, Central Kalimantan, and Maluku are three regions representing parts of Indonesia that have a variety of rainfall distribution and climatic conditions. This research was conducted to determine the influence of the El Nino and La Nina climate anomalies on these three regions by looking at the areas that have a dominant influence due to these climate anomalies. The research used BMKG Indonesia rainfall data with a total of 16 rainfall stations and a data range of 22 years. The methods used for modeling are the Fast Fourier Transform (FFT) and Lomb Periodogram to obtain rainfall spectrum data. Then, the amplitude value was obtained, and a comparison of the data from the two methods was carried out to determine the recurrence value and the area with the highest impact due to climate anomalies. The results of data analysis according to the FFT and Lomb Periodogram showed that the highest affected area was the eastern part of Indonesia, namely Maluku Province, with the dominant frequency according to the FFT method being 5.61 years with a PSD of 7.67 mm2 and the Lomb Periodogram 6.06 years with a PSD of 18.64 mm2. Based on the average PSD value, using both FFT and Lomb Periodograms, it also shows that the influence of El Nino and La Nina is greatest in the eastern part of Indonesia; as you move towards the west, this influence decreases. The smallest influence occurred in western Indonesia. This shows that the influence of ENSO is more dominant than the influence of IODM.